Pengaruh Pelatihan terhadap Peningkatan Pengetahuan Kader Posyandu tentang Deteksi Dini TBC Anak di Kelurahan Tanjung Mas Semarang - Eti Rimawati; Sri Handayani; Catur Yuantari (ABDIMASKU : JURNAL PENGABDIAN MASYARAKAT, 2021)
Symptoms of tuberculosis in children that are not specific require early detection efforts. One of the efforts to carry out early detection is to monitor children's growth and development in posyandu activities. Posyandu cadres have an important role in this. The purpose of this training activity is to increase the knowledge of posyandu cadres in early detection of tuberculosis in children. The target of the training was 21 posyandu cadres who were selected by purposive sampling. Training activities as a form of community service are carried out with the stages of giving a pretest, presentation of material and case and posttest questions. The Wilcoxon Signed Rank Test analysis is used to determine differences in knowledge before and after training. All cadres were female, with the lowest education was junior high school (9.8%), the youngest was 38 years old and the oldest was 65 years old. The results of the difference test showed that there was a difference between before and after training (p value 0.0006), indicating that the training method was effective in increasing the knowledge of the cadres